Perkembangan Pendidikan Islam di Minangkabau: Perguruan Islam Ar Risalah 2003-2018 - Suyatna Syah Putra; Erniwati Erniwati; Abdul Salam (Galanggang Sejarah, 2019)
Islamic education in Minangkabau always develops each year. One of the Islamic education institutes that support this developing is Perguruan Islam Ar Risalah, Padang City. Perguruan Islam Ar Risalah is a part of donating institution, Islam Ar Risalah. This institution was held on June, 24th 2003 by LIPIA alumnus. In the beginning, this institution only focuses on one level of education, junior high school. But, after that time, this institution expands to some levels of education, there are kindergarten, elementary school, senior high school, Ma’had ‘aly, and Ar Risalah economic school of Islam. In this paper, we focus on the history of how the institution exists, strategic, to develop their institution and influence of this institution for social and religion of around society. The method of this paper is the historical method. The steps are heuristic/gathering the data, then verification of critical for getting the real information from the source. Then interpretation (re-understanding) about the data. And the last, presenting the result to create the paper about the history of Perguruan Islam Ar Risalah.